2017
DOI: 10.1001/jamafacial.2016.1666
|View full text |Cite
|
Sign up to set email alerts
|

Universal Trichloroacetic Acid Peel Technique for Light and Dark Skin

Abstract: IMPORTANCE Despite their great potential, medium and deep trichloroacetic acid peels are underused in light-skinned patients and are rarely used in darker-skinned patients because of the widespread fear of pigmentary complications and scarring. This concern has led many physicians to opt for the use of lighter types of peels (glycolic acid peel, Jessner peel, etc) and different lasers and intense light technologies. Trichloroacetic acid peels have been described in numerous publications. However, no study to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…A large-scale retrospective study on 923 patients receiving 35-45% TCA peel grouped patients by ethnicity rather than FST and found that 5.9% experienced persistent hyperpigmentation that occurred primarily in the Asian and Indo-Pakistani population. The study also found a single African patient that experienced hypopigmentation [62].…”
Section: Trichloroacetic Acidmentioning
confidence: 65%
“…A large-scale retrospective study on 923 patients receiving 35-45% TCA peel grouped patients by ethnicity rather than FST and found that 5.9% experienced persistent hyperpigmentation that occurred primarily in the Asian and Indo-Pakistani population. The study also found a single African patient that experienced hypopigmentation [62].…”
Section: Trichloroacetic Acidmentioning
confidence: 65%
“…TCA is used for several treatment purposes in dermatology practice including actinic damage, warts, acne scars, and cosmetic peels . Several mechanisms of action underlying these applications have been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Chemical peeling is a well‐known cosmetic technique based on the topical application of different agents such as: salicylic acid, glycolic acid, pyruvic acid, lactic acid, mandelic acid, Jessner solution, TCA, and phenol, in variable concentrations and combination (Kontochristopoulos & Platsidaki, ). Seventy percent TCA peels have been reported to be safe in cosmetic practice, even in light‐skinned patients, where the risk of hyperpigmentation can be high when it is applied on large area of the face (Fanous & Zari, ).…”
Section: Discussionmentioning
confidence: 99%